واقع البرامج والخدمات المقدمة في مؤسسات ومراكز التربية الفكرية في منطقة حائل بالمملكة العربية السعودية في ضوء المعايير العالمية - الخطيب، عاكف عبدالله موسى; الشرمان، وائل محمد (جامعة الأزهر - كلية التربية, 2016)
This study aimed to assess the level of effectiveness of the programs and services provided in institutions and intellectual education centers in Hail in Saudi Arabia according to the international standards. The study sample consisted of all institutions and intellectual education centers in Hail with a number of (26) Centers and institutions. In order to achieve the purpose of this study, a checklist was built to assess the level of programs and services in institutions and intellectual education centers.\\ The results, regarding the intellectual disability, indicated that there was only one dimension with a very high level of effectiveness programs and services with an average of 0.75), While there were three dimensions with a medium level of effectiveness respectively learning environmen with an average of (0.66),evaluation with an average of (0.55), and management and staff with an average of (0.47). The rest of the dimensions, low effectiveness dimensions, were vision, thought and the mission with an average of (0.33), and the participation, support, and empowerment of the family with an average of (0.31).
هدفت هذه الدراسة إلى تقييم مستوي فاعلية البرامج والخدمات المقدمة في مؤسسات ومراكز التربية الفكرية في منطقة حائل في ضوء المعايير العالمية، وتكونت عينة الدراسة من جميع المؤسسات ومراكز التربية الفكرية في منطقة حائل وعددها (26) مركز ومؤسسة، ولتحقيق هدف الدراسة فقد تم بناء أداة لتقييم مستوي البرامج والخدمات في مؤسسات ومراكز التربية الفكرية. وقد أشارت النتائج أن هناك بعدا واحدا كان ذا مستوي فاعلية مرتفع وهو: "بعد البرامج والخدمات " وبمتوسط حسابي (0.75)، في حين أن هناك ثلاثة أبعاد كانت ذات مستوي فاعلية متوسطة وهي على التوالي: بعد "البيئة التعليمية" بمتوسط حسابي (0.66)، وبعد "التقييم" بمتوسط حسابي (0.55)، وبعد "الإدارة والعاملين" بمتوسط حسابي (0.47). وباقي الأبعاد وعددها اثنان كانت ذات مستوي فاعلية متدنية وهي بعد "الرؤية والفكر والرسالة" بمتوسط (0.33)، و "مشاركة ودعم وتدعيم وتمكين الأسرة بمتوسط (0.31).
Keywords: الخدمات التربوية -- التربية الخاصة -- المملكة العربية السعودية -- الإعاقة العقلية